(untitled) (Biological Sciences - PJSIR, 2000)
During low temperature crystallization studies of magnesium sulphate from sea bittern, the time temperature plots have been found to be linear. This uncommon phenomenon in unsteady state operation has been explained through modified energy balance equation in terms of rate of overall heat changes associated with crystallization, characteristic properties of raw material, overall averages temperature drop and system constants. While explaining the linearity of the plots, the authors have not only deduced a law concerning low temperature crystallization and the conditions in which it is operative but also derived relationships for estimating heat of crystallization, heat transfer co-efficient and heat utilization co- efficient. It is observed that the composition of raw material (bittern) has a direct effect on specific heat and slope of temperature-time relationship, whereas heat of crystallization is governed by the type of sample used heated or normal.The numerical results have also established that it is rather the design of the cooling unit (chiller) which governs its efficiency whereas increase in chilling capacity enhances the output only (heat transfer co-efficient). Further, the statistical analysis of the numerical data revealed that in different situations it is not only normally distributed but also found substantiating the conclusions drawn from the observed data.